Сенсорный модуль с алмазоподобными электродами системы электрохемилюминесцентного анализа биопроб - Семеней, А. М.; Рожицкий, H. H. (ХНУРЭ, 2008)
In this work the problem of liquid biological sample analysis by developed electrochemiluminescence unit with diamond-like films on working electrode and sample transport system based on the electrokinetic’s phenomena is. considered. Its use for definition of concentration of bilirubin in blood that is necessary for diagnostics of bilious system pathologies is considered.
Keywords: анализ биопроб; сенсорный модуль